β-Synuclein as a candidate blood biomarker for synaptic degeneration in Alzheimer’s disease - Pablo Mohaupt; Marie-Laure Pons; Jérôme Vialaret; Constance Delaby; Christophe Hirtz; Sylvain Lehmann (Alzheimer’s Research & Therapy, 2022)
Abstract Synaptic degeneration is an early event closely associated with the course of Alzheimer’s disease (AD). The identification of synaptic blood biomarkers is, therefore, of great interest and clinical relevance. The levels of most synaptic proteins are increased in the cerebrospinal fluid (CSF) of patients with AD, but their detection in blood is hitherto either unavailable or not very informative. This paradigm is related to their low concentration, their peripheral origin, or the presence of highly abundant blood proteins that hinder detection. In recent years, significant progress has been made in detecting the presynaptic protein β-synuclein. This mini-review summarizes the results that highlight the role of β-synuclein as a candidate blood marker for synaptic degeneration in AD.